Teknik Reinforcement dalam Menurunkan Perilaku Agresif pada Anak Usia Dini - Lathifatul Fajriyah (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The purpose of this study is to reduce aggressiveness in early childhood, especially 5-6 years of age. This research is a quasi-experiment research with Nonequivalent control group design, data collection techniques using observation and documentation. The population in this study were 2 classes, namely group B1 and group B2 with random sampling technique, each of which had 15 students. Data collection techniques using observation and documentation. The instrument measurement scale uses a Likert scale. The data analysis technique uses the t test, namely independent sample t-test and paired sampe-test to determine the comparison when the pretest and postest. The data was processed using the help of SPPS for windows to determine whether the hypothesis was rejected or accepted. The results showed that after treatment for 5 times, it can be seen from the results of calculations with SPSS which obtained a value of 0.000 which means the sig value <0.05. This means that there is an effect of reinforcement techniques in reducing the level of aggressiveness of Ramadani natural school children. Forms of aggressiveness in children such as pushing, grabbing, ignoring teacher calls, hitting.